2015
DOI: 10.3892/etm.2015.2227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fentanyl, midazolam and their combination on immune function and mortality in mice with sepsis

Abstract: The aim of this study was to investigate the effects of fentanyl and/or midazolam on the immune function and mortality of septic mice. Mice were randomly divided into sham-operated, model, fentanyl-, midazolam- and combination-treated groups. The body weights and locomotor activities of the mice were measured, prior to and following surgery, and the mortality rates following surgery were recorded and compared among these groups. The organ weights and the corresponding coefficients were measured and calculated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
(17 reference statements)
0
9
1
Order By: Relevance
“…Opioid agent fentanyl is one of the most commonly clinically used analgesic and sedative drugs. In recent years, the immunomodulatory effects of opioids were presented in many tissues and diseases, including surgery , cancer and infections . However, little is known about the effects of fentanyl on immune responses in parturition and post‐partum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opioid agent fentanyl is one of the most commonly clinically used analgesic and sedative drugs. In recent years, the immunomodulatory effects of opioids were presented in many tissues and diseases, including surgery , cancer and infections . However, little is known about the effects of fentanyl on immune responses in parturition and post‐partum.…”
Section: Discussionmentioning
confidence: 99%
“…Fentanyl, a kind of synthetic opioid, has been widely used for anaesthesia and analgesia. It has been demonstrated to reduce inflammatory responses in septic mice , decreased regulatory T cells (Tregs) number in vitro and inhibit the expression of proinflammatory cytokines, including IL‐6, IL‐10 and tumour necrosis factor (TNF)‐ α , in lipopolysaccharide (LPS)‐induced inflammation . Little is known about the effects of fentanyl on immune responses in the immune recovery during the process of labour and post‐partum.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence and development of sepsis are caused by an imbalance of pro-inflammatory and anti-inflammatory mechanisms ( 29 ). When the disease develops to a certain degree, the body’s immune function is inhibited to various degrees, which eventually leads to a highly lethal immune disorder that is characterized by immune cell apoptosis and severe paralysis ( 30 ). The large decrease in the number and function of immune cells through apoptosis is one of the major causes of the high mortality in patients with severe sepsis ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the levels of proinflammatory cytokines are reduced by fentanyl and/ or midazolam, which may contribute to the beneficial effects of these medications in septic mice. Additionally, analgesia can reduce inflammatory responses in septic mice, resulting in immunosedation and contributing to improved outcomes and mortality rates in murine sepsis (42). While we did use antibiotics for the survival studies, we did not use antibiotics for the short-term, 20-hour experiments.…”
Section: Methodsmentioning
confidence: 99%